Medical Students' Attitude to wards Anatomy Dissection: A Study from Nepal - Sharma, Nitasha; Subedi, S; Pandit, R (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: Among medical education institutions worldwide, the time allotted for anatomy instruction has decreased without any reasonable time optimization suggestions. In addition, the utility of cadaver dissection has long been debated.MATERIAL & METHODS: This study was conducted to determine the attitudes of preclinical students to cadaver dissection in the study of human anatomy. A collection of questionnaire was introduced to 290 preclinical students, including both MBBS and BDS of Universal College of Medical Sciences, Nepal. For each question, the students were to choose one of the three possible responses: “yes”, “no” or “undecided”. Out of the 290 students (162 female and 128 male) involved in the study.RESULTS: Fifty five percentage said they were curious, 41% experience of anatomy dissection hall was interesting, 3% said it was enj oyable and remaining 1% said it was boring. An analysis of the questionnaire showed that a vast majority of the students (93%) considered cadaver dissection as important and indispensable in the study of human anatomy, on the issue of replacing cadaver dissection with plastic models in the near future, majority of the students under study (73%) didn't favored such a replacement, while 24% did. In the present study, 29% of students mentioned there was not enough chances of dissection for every individual students and 40% of students said the time allocated for dissection classes was not enough.CONCLUSION: From the results of the present study, one might confidently infer that cadaver dissection is still considered important and indispensable in the study of human anatomy.Journal of Universal College of Medical Sciences, Vol. 5, No, 2, 2017, Page: 12-17